Finding the path - women entrepreneurs, micro and small scale enterprises and their path to growth in Dar es Salaam, Tanzania - Rubin,Erika (2011)
This study of ten micro and small scale businesses owned and management by Tanzanian women in Dar es Salaam aimed at fulfilling two purposes; to highlight male biased assumptions and gender blindness in the discourse and discursive practices on entrepreneurship as well as exploring women’s own perceptions of identity and gender. The second more straight forward empirical purpose was exploring women entrepreneurs pathways to growth, but still taking in to account how structural gendered processes affects and is affected by this pathway, the strategies and goals. Using a theoretical framework building on hegemonic masculinity theory, entrepreneurial mentality and the entrepreneur as based on a male norm and the 5M framework (including the dimensions of Markets, Money, Management, Motherhood and Macro and meso environment) it was found that contextual elements i.e. social, cultural and economical dimensions as well as gendered divisions of labour in the household influence women’s identities and entrepreneurship. It was concluded that women’s pathways to growth was dependent on access to skills development, family support and team work with staff among other things. Through adopting the discursive practices on entrepreneurial mentality that are gendered and based on male idealised stereotypes, and adapting these to their own experiences, what they see around themselves, the women interviewed turn the concept of the entrepreneur in to something different.
Keywords: Entrepreneurship; gender; women; masculinity; micro and small enterprises; growth